Study on Sex Determination and Impact of Sex Ratio to Reproduction Success in Black Soldier Fly - Ramadhani Eka Putra; Nindia Safa'at (Jurnal Biodjati, 2020)
Black soldier fly (BSF) (Hermetia illucens) is an insect spe-cies utilized as the converter of organic wastes into biomass applicable as a potential replacement of protein and lipid sources of animal feed and other industrial use. The limiting factor for the sus-tainability of this activity is the number of eggs produced as all processes started from the egg. Variable of quality of the substrate eaten during the larval stage and the proportion of males and fe-males are among the decisive factors for egg production. The pur-poses of this study were to understand the impact of the substrate to the production of a particular sex, to developed a simple method by comparing the weight and size of the pupae to distinguished between male and female, and to find the best sex ratio to produce the highest number of eggs. In this study, two types of substrates (balance proportion of macronutrient and high in protein and lipid were applied as feeding material for larvae. The weight and length of each pupa produced were measured and the pupae kept inside separated containers to find the morphological differences between male and female pupae. Adult insects produced from pupae then used for study on the effect of sex ratio on reproduction success. The adults kept inside 1 x 1 x 1 m screen cages with 3 groups of sex ratio (male : female) which were 50%:50% (P1), 60%:40% (P2), and 40%:60% (P3). The probability of sex was analyzed by logistic regression while the number of eggs estimated by the weight of the egg batch. The result showed substrate used in this study is not affect the sex ratio of adult flies, weight of pupae as the best predictor for sex of the adult flies, and the best ratio of male and female for egg production was 40:60.